ANALISIS PERTUMBUHAN TUNAS LIDAH BUAYA (Aloe Vera) YANG BERASAL DARI BERBAGAI PENANGKAR PADA LAHAN BERPASIR - Ari jumanto; Rennanti Lunnadiyah Aprilia (Yayasan Nusantara Hasana Berdikari, 2025)
Aloe vera is a tropical plant with high economic value in health, cosmetics, and agricultural industries. This study aims to analyze the shoot growth of Aloe vera var. chinensis on sandy soil and determine the best seedling source based on plant growth performance. The research was conducted in Tegalretno Village, Petanahan District, Kebumen Regency, from August to November 2024, using a Completely Randomized Block Design (CRBD) with a non-factorial approach. Five seedling sources (Gunung Kidul, Bantul, Purbalingga, Cilacap, and Kebumen) were tested with five replications. Data were analyzed using DMRT at a 5% significance level. The results showed that treatment A3 (Purbalingga seed source) exhibited the best shoot growth parameters, including the highest number of shoots (3.3125 shoots), the highest number of leaflets per shoot (6.771833 leaflets), and the tallest leaflet height (22.3708 cm). In terms of overall plant growth, A3 also performed well in plant height (45.975 cm) and leaf circumference (13.675 cm). Meanwhile, treatment A1 (Gunung Kidul) excelled in leaf length (43.15 cm). The lowest growth performance was observed in A2 (Bantul). Genetic factors and environmental adaptation played crucial roles in shoot development. Based on these findings, the Purbalingga seed source (A3) is recommended for cultivating Aloe vera in sandy soil conditions.